Research of some psychical qualities of cadets' personality with the aid of psychogeometric test - Afonin V.M; Kuprinenko O.V (Kharkov National Pedagogical University, 2010)
The results of application of psychogeometric test are given. A test is used studies of some properties of personality of students of military institute. 298 students of different soldiery specialities took part in researches. It is rotined that considerable part of students (including speciality physical education) behave to the psychological types of man with the lines of peaceable disposition, connectivity, unconflict, ideological content. The representatives of basic soldiery specialities (airmobile troops) aim to be leaders in a collective, to win, be successful.